TDP2 suppresses chromosomal translocations induced by DNA topoisomerase II during gene transcription - Gómez-Herreros, Fernando (Nat Commun, 2017)
DNA double-strand breaks (DSBs) induced by abortive topoisomerase II (TOP2) activity are a potential source of genome instability and chromosome translocation. TOP2-induced DNA double-strand breaks are rejoined in part by tyrosyl-DNA phosphodiesterase 2 (TDP2)-dependent non-homologous end-joining (NHEJ), but whether this process suppresses or promotes TOP2-induced translocations is unclear. Here, we show that TDP2 rejoins DSBs induced during transcription-dependent TOP2 activity in breast cancer cells and at the translocation ‘hotspot’, MLL. Moreover, we find that TDP2 suppresses chromosome rearrangements induced by TOP2 and reduces TOP2-induced chromosome translocations that arise during gene transcription. Interestingly, however, we implicate TDP2-dependent NHEJ in the formation of a rare subclass of translocations associated previously with therapy-related leukemia and characterized by junction sequences with 4-bp of perfect homology. Collectively, these data highlight the threat posed by TOP2-induced DSBs during transcription and demonstrate the importance of TDP2-dependent non-homologous end-joining in protecting both gene transcription and genome stability.